Deep resilience: An evolutionary perspective on calcification in an age of ocean acidification - Gold, David A.; Vermeij, Geerat J. (Frontiers in Physiology, 2023)
The success of today’s calcifying organisms in tomorrow’s oceans depends, in part, on the resilience of their skeletons to ocean acidification. To the extent this statement is true there is reason to have hope. Many marine calcifiers demonstrate resilience when exposed to environments that mimic near-term ocean acidification. The fossil record similarly suggests that resilience in skeletons has increased dramatically over geologic time. This “deep resilience” is seen in the long-term stability of skeletal chemistry, as well as a decreasing correlation between skeletal mineralogy and extinction risk over time. Such resilience over geologic timescales is often attributed to genetic canalization—the hardening of genetic pathways due to the evolution of increasingly complex regulatory systems. But paradoxically, our current knowledge on biomineralization genetics suggests an opposing trend, where genes are co-opted and shuffled at an evolutionarily rapid pace. In this paper we consider two possible mechanisms driving deep resilience in skeletons that fall outside of genetic canalization: microbial co-regulation and macroevolutionary trends in skeleton structure. The mechanisms driving deep resilience should be considered when creating risk assessments for marine organisms facing ocean acidification and provide a wealth of research avenues to explore.